THE USE OF ARTICULATION LEARNING MODELS IN PAI SUBJECTS AT SMPN 1 PONTANG, BANTEN - Wasehudin Wasehudin; Irfan Anshori; Marzuki Marzuki (JURNAL ILMIAH DIDAKTIKA: Media Ilmiah Pendidikan dan Pengajaran, 2022)
This study aims to determine the application of the articulation learning model at SMP Negeri 1 Pontang, especially in the subject of Islamic Religious Education. The method used is a qualitative method using SWOT analysis. The approach in this study is presented descriptively. This research was conducted at SMP Negeri 1 Pontang, Pontang District, Serang Regency, Banten Province. This research explains in detail the flow of articulation learning and also presents about Strenght, Weaknesses, Opportunities and Threats. The results of this study show that the articulation learning model on the strength aspect can train students' absorption and train students' readiness. On the aspect of weakness, this learning model can only be used by certain subjects. The opportunity aspect of this learning model, students are trained in speaking, can speak loudly and clearly. Meanwhile, on the threat aspect, this learning model can not be completed if a teacher is not able to manage learning time, because the articulation learning model requires a lot of time. With the implementation of the articulation learning model in PAI subjects, there are no longer students who think that PAI subjects are boring subjects.